Profiling clusters of European electricity markets - Cardoso, M. G. M. S.; Martins, A. A. A. F.; Lagarto, J. (JOCLAD 2020, 2020)
We aim to characterize clusters of European regions with similar electricity prices behavior. Since electricity prices are influenced by many drivers such as demand, fuel and CO2 emission allowances prices and renewable and nonrenewable energy production, we integrate in the analysis, time series data regarding multiple related predictors. The insights on the clusters are obtained via descriptive and exploratory techniques including classification trees. Auxiliary analysis includes building adequate features from time series (e.g. Discrete Fourier transform are considered).